Solve for y 6y-6<=-x

Math
6y-6≤-x
Add 6 to both sides of the inequality.
6y≤-x+6
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6y≤-x+6 by 6.
6y6≤-x6+66
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6y6≤-x6+66
Divide y by 1.
y≤-x6+66
y≤-x6+66
Simplify each term.
Tap for more steps…
Move the negative in front of the fraction.
y≤-x6+66
Divide 6 by 6.
y≤-x6+1
y≤-x6+1
y≤-x6+1
Solve for y 6y-6<=-x

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top